2022
DOI: 10.1038/s41598-022-12707-2
|View full text |Cite
|
Sign up to set email alerts
|

Personality and fatigue: meta-analysis of seven prospective studies

Abstract: The present study examined the cross-sectional and longitudinal associations between the five major personality traits and fatigue. Participants were adults aged 16–104 years old (N > 40,000 at baseline) from the Health and Retirement Study, the National Social Life, Health, and Aging Project, the Wisconsin Longitudinal Study graduate and sibling samples, the National Health and Aging Trends Survey, the Longitudinal Internet Studies for the Social Sciences and the English Longitudinal Study of Ageing. Perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
(118 reference statements)
1
2
1
Order By: Relevance
“…Incerti et al [79] reported that personality traits such as depression, avoidance, addiction, and masochism were related to high fatigue levels. Moreover, histrionicism and narcissism were negatively related to fatigue, unlike in other studies, in which the high neuroticism, loss of empathy, and low pleasantness, elements characterizing high narcissism and histrionicism, correlated directly with fatigue [122,123].…”
Section: Discussioncontrasting
confidence: 90%
“…Incerti et al [79] reported that personality traits such as depression, avoidance, addiction, and masochism were related to high fatigue levels. Moreover, histrionicism and narcissism were negatively related to fatigue, unlike in other studies, in which the high neuroticism, loss of empathy, and low pleasantness, elements characterizing high narcissism and histrionicism, correlated directly with fatigue [122,123].…”
Section: Discussioncontrasting
confidence: 90%
“…A potential mechanism explaining this relationship could be related to general behavioral attitudes, observed especially in social contexts [ 55 ]. In line with other results, extraversion and openness proved to have a negative correlation with pain and fatigue perception [ 56 , 57 ]. Nonetheless, emotional stability was specifically related to depression in our research.…”
Section: Discussionsupporting
confidence: 90%
“…Vice versa, the lower the level of neuroticism trait personality, the lower the social media fatigue experienced by early adulthood. Research conducted by Stephan et al [33] showed that neuroticism, information overload, invasion of life, and anxiety are all associated with social media fatigue. Excess information is the most dominant antecedent in influencing the occurrence of social media fatigue in students.…”
Section: Discussionmentioning
confidence: 99%